If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -23p + -6(3 + -5p) = 5(p + -2) + -14 -23p + (3 * -6 + -5p * -6) = 5(p + -2) + -14 -23p + (-18 + 30p) = 5(p + -2) + -14 Reorder the terms: -18 + -23p + 30p = 5(p + -2) + -14 Combine like terms: -23p + 30p = 7p -18 + 7p = 5(p + -2) + -14 Reorder the terms: -18 + 7p = 5(-2 + p) + -14 -18 + 7p = (-2 * 5 + p * 5) + -14 -18 + 7p = (-10 + 5p) + -14 Reorder the terms: -18 + 7p = -10 + -14 + 5p Combine like terms: -10 + -14 = -24 -18 + 7p = -24 + 5p Solving -18 + 7p = -24 + 5p Solving for variable 'p'. Move all terms containing p to the left, all other terms to the right. Add '-5p' to each side of the equation. -18 + 7p + -5p = -24 + 5p + -5p Combine like terms: 7p + -5p = 2p -18 + 2p = -24 + 5p + -5p Combine like terms: 5p + -5p = 0 -18 + 2p = -24 + 0 -18 + 2p = -24 Add '18' to each side of the equation. -18 + 18 + 2p = -24 + 18 Combine like terms: -18 + 18 = 0 0 + 2p = -24 + 18 2p = -24 + 18 Combine like terms: -24 + 18 = -6 2p = -6 Divide each side by '2'. p = -3 Simplifying p = -3
| 8k+8k= | | 2(m-8)=4 | | 4/7a=8 | | 9w-8w+8=11-2 | | 4t^3=108 | | 84+6h=114 | | -5x-24=4x+12 | | 4n^2-25=0 | | -44=n+8 | | (7x+1)(9x^2+4x+5)= | | n/3+4=10 | | M/3-14=10 | | 5y+5=4y-4 | | 0.22-0.02(x+3)=0.02(2-x) | | 6-wx=vx+2 | | 3=6+x/4 | | 9+(0.5x)= | | -5x+3=8 | | x(x-7)=458 | | 2/5y+3=6 | | 0.12-0.01(x+3)=-0.03(1-x) | | Y/3+25=48 | | 3/4p+7=16 | | 3/x=2/x-1 | | 31+w/3=31 | | k/8-9=6 | | 32+90x=78x+78 | | x/5-3=x/7-1 | | 4x+43=139 | | 22x+8x=160+22x | | 8(2x+1)-(x+3)=35 | | 39+3m=174 |